Students’ Perception toward Teacher’s Talk in English Teaching-Learning Process - Bambang Iswan (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2016)
The aim of this research is to investigate: 1) How are the students’ perceptions about kinds of English teacher’s talk in English teaching-learning process?, and 2) How many percentages of kinds of teacher’s talk are used by the English teacher in English teaching-learning process?. This research used descriptive quantitative method. The population was the tenth grade students of Islamic Senior High School (Madrasah Aliyah) Darul Amal Tunggang, Pondok Suguh District, Mukomuko Regency, Bengkulu Province, Indonesia in academic year 2014/2015 with total number of students are 15 students. The researcher took all of the students as sample of the research. This descriptive quantitative research was used questionnaire and observation checklist as the instrument to gather the data. It was included from ten categories kinds of teacher’s talk. The results of data were analyzed by using weight average formula. The findings showed that: 1) The students’ perception toward their teacher’s talk in English teaching-learning process was positive (3.41=Agree), and 2) The kind of teacher’s talk which the English teacher express during English teaching-learning process from the mostly often to rarely are: convergent question (22.22%), inform feedback (16.66 %), divergent question (12.96%), summarizing feedback (11.11%), praising feedback (9.25%), procedural question (7.40%), ignoring feedback (7.40%), prompt feedback (5.55%), encouragement feedback (3.70%) and criticizing feedback (3.70%).